2019
DOI: 10.35741/issn.0258-2724.54.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Solar Cells Using Novel Micro- and Nano-Complexes of Triazole Schiff Base Derivatives

Abstract: A new asymmetrical Schiff base triazole ligand, (4-(((3-mercapto-5-(naphthalen-1-ylmethyl)-4H-1,2,4-triazol-4-yl)imino)methyl)phenol) (L1), was synthesized and characterized using CHNS elemental analysis and FTIR, UV/Vis, mass, 1H NMR, and 13C NMR spectroscopies. The Schiff base metal complexes of NiL1, PdL1, and AgL1 were synthesized and identified using FTIR, UV/Vis and flame atomic absorption spectroscopies and elemental analysis, as well as magnetic susceptibility and conductivity measurements. NanoL1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…TMCs drugs (TMCD) have become increasingly important in inorganic and medicinal chemistry and have attracted a great deal of attention over the past decade in drug development strategies [4,5]. The studies have also shown that the nanomaterials and nanocomplexes have distinctive physical, chemical and biological applications [6][7][8][9][10][11][12][13][14][15][16][17]. Theophylline, 1,3-dimethylxanthine, with significant biological characteristics, is a purine alkaloid.…”
Section: Introductionmentioning
confidence: 99%
“…TMCs drugs (TMCD) have become increasingly important in inorganic and medicinal chemistry and have attracted a great deal of attention over the past decade in drug development strategies [4,5]. The studies have also shown that the nanomaterials and nanocomplexes have distinctive physical, chemical and biological applications [6][7][8][9][10][11][12][13][14][15][16][17]. Theophylline, 1,3-dimethylxanthine, with significant biological characteristics, is a purine alkaloid.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal complexes drug (TMCD) have become increasingly important in inorganic and medicinal chemistry and have attracted a great deal of attention over the past decade in drug development strategies [6]. Nanotechnology plays an important role in inorganic chemistry through the formation of nano complexes and nano oxides, which are included in many biological and industrial applications [7][8][9][10][11][12][13][14][15][16][17][18]. Theophylline (Scheme 1) transition metal complexes can be used to analyze the relationship as template compounds between metal ions and nucleic acid oxo purine bases [19].…”
Section: Introductionmentioning
confidence: 99%
“…The particular physical and chemical characteristics of nanomaterials are common in all areas [19][20][21][22][23]. The nano complexes have appropriate physical, chemical, and biological applications as studies have shown [24,25].…”
Section: Introductionmentioning
confidence: 99%